Sport marketing - Dees, Windy PhD 1977-; Mullin, Bernard James PhD; Hardy, Stephen 1948- PhD; McEvoy, Chad D. EdD 1971-; McKelvey, Stephen 1959- JD; Sutton, William Anthony 1951- EdD; Walsh, Patrick PhD 1978- (Human Kinetics, Inc., 2022)
This book helps students prepare for careers in the fast-paced world of sport marketing, as well as provides a resource for practitioners looking for the latest information in the field. The book offers abundant examples of the latest issues in the competitive marketplace